STRATEGI PEER LESSON DALAM MATA PEMBELAJARAN ALQURAN-HADITS - Ahmad Aziz Fanani (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
The purpose of this research are identified and analyzed the forms of learning activities that are implemented in MTs Negeri 8 Banyuwangi by the Peer Lesson learning strategy, the obstacles experienced and the solution of it. The type of research used qualitative research methods with purposive sampling technique have done in MTs Negeri 8 Banyuwangi. The Researchers use source and methode triangulations as data validity. Data analysis techniques using structured interviews, active participatory observation and documentation. The results that the Peer Lesson learning strategy is learning that focuses students as another student tutors with the step begin of preparation, implementation, and evaluation. However, some obstacles in this implementation include the lack of readiness of students to participate in learning, lack of self-confidence in students, more prominent students who are active than those who are less active, learning practices related to the duration of learning are a little less appropriate because of it longer duration compared to initial planning. And it has been found several solutions to these obstacles include suggestions for students to always read the material to be discussed, the motivation of the teacher before learning, giving students the task of making a question and summarizing the material being discussed individually, maximizing the skills and expertise possessed by the teacher.